2010
DOI: 10.1172/jci39481
|View full text |Cite
|
Sign up to set email alerts
|

NOD1 contributes to mouse host defense against Helicobacter pylori via induction of type I IFN and activation of the ISGF3 signaling pathway

Abstract: Nucleotide-binding oligomerization domain 1 (NOD1) is an intracellular epithelial cell protein known to play a role in host defense at mucosal surfaces. Here we show that a ligand specific for NOD1, a peptide derived from peptidoglycan, initiates an unexpected signaling pathway in human epithelial cell lines that results in the production of type I IFN. Detailed analysis revealed the components of the signaling pathway. NOD1 binding to its ligand triggered activation of the serine-threonine kinase RICK, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
264
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(285 citation statements)
references
References 64 publications
(90 reference statements)
13
264
0
3
Order By: Relevance
“…Similarly, in another study, IKKβ was not required for NOD1 activation of IFN signaling in an H. pylori model. Although the role of IKKα was not studied in that model, the induction of IFN through NOD1 signaling was found to depend on TBK1 and IKKe (34). Nuclear translocation of NF-κB is a direct response to Tri-DAP-stimulated NOD1 (26), and is dependent on IKKα (28).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, in another study, IKKβ was not required for NOD1 activation of IFN signaling in an H. pylori model. Although the role of IKKα was not studied in that model, the induction of IFN through NOD1 signaling was found to depend on TBK1 and IKKe (34). Nuclear translocation of NF-κB is a direct response to Tri-DAP-stimulated NOD1 (26), and is dependent on IKKα (28).…”
Section: Discussionmentioning
confidence: 96%
“…As bacterial sensors, NOD1 and NOD2 induce downstream signaling pathways. Although NF-κB is a major signaling pathway downstream of NOD1 and NOD2, type I IFNs were induced via NOD1 during infection with H. pylori, reminiscent of an antiviral response (34). NOD2-dependent IFN-β production during infection with Listeria resulted from synergy with other cytosolic microbial sensors (11).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent in vitro mechanistic studies have shown that the effects of NOD1 on IFN production appear to be independent of IRF3, based on a lack of ssRNA-induced IRF3 activation and IFN-b signalling (Sabbah et al, 2009). Indeed, the interactions of NOD1 with IRF7 via the RICK/TRAF3/TBK1/ IKK1 cascade appears to be the major mechanism of NOD1 IFN stimulation, which previously has been shown in Helicobacter pylori studies (Watanabe et al, 2010(Watanabe et al, , 2011. In addition to its effects on innate immune signalling, NOD1 has also been suggested to play a significant role in linking the innate and adaptive immune responses following virus exposure.…”
Section: Introductionmentioning
confidence: 85%
“…Initially, we found that stimulation of gastrointestinal ECs with NOD1 ligands leads to robust production of pro-inflammatory Th1 chemokines such as IP-10 (IFNγ-induced protein of 10 kDa). 17 Given the fact that, as mentioned above, NFκB activation was not a major player in the induction of these chemokines we sought the TLR or NLR mechanism and the latter results in IL-17 production. 14 Given the fact that H. pylori organisms cause a non-penetrating superficial infection of the gastric mucosa and gastric APCs reside in the submucosal areas, it is likely that innate immune responses mediated by H. pylori-stimulated gastric ECs play an important role in the immunopathogenesis of H. pylori-associated gastric diseases.…”
Section: Activation Of Type I Ifn Signaling By Nod1mentioning
confidence: 99%